Eye Movement Desensitization and Reprocessing in der Behandlung psychosomatischer Störungsbilder - Vock, Stephanie; Tesarz, Jonas (Die Psychotherapie, 2025)
Eye movement desensitization and reprocessing (EMDR) was developed in the late 1980s for the treatment of posttraumatic stress disorders (PTSD). The method is now also used for mental disorders outside of classical PTSD. The theoretical principles based on the model of adaptive information processing (AIP), postulates that psychological disorders are caused by inadequately processed traumatic memories. Using bilateral stimulation of the brain in the form of eye movements, the integration of inadequately processed memories is supported and emotional effects are reduced. This overview article provides a comprehensive description of the process and content of EMDR. The theoretical background in the treatment of psychosomatic disorders is presented and the fields of application of EMDR outside the treatment of PTSD are described. The article highlights the growing importance of EMDR in psychosomatics and discusses the diverse applications.